Anti-inflammatory Trained Immunity Mediated by Helminth Products Attenuates the Induction of T Cell-Mediated Autoimmune Disease - Quinn, Shauna M.; Cunningham, Kyle; Raverdeau, Mathilde; Walsh, Robert J.; Curham, Lucy; Malara, Anna; Mills, Kingston H. G. (Frontiers in Immunology, 2019)
Recent studies have suggested that the innate immune system can display characteristics of immunological memory and this has been called ‘innate immune memory’ or ‘trained immunity’. Certain fungal products have been shown to induce epigenetic imprinting on monocytes/macrophages that results in heightened inflammatory responses to subsequent stimulus. Here we report that innate immune cells can be trained to be more anti-inflammatory following exposure to products of a helminth pathogen. Macrophages trained in vitro with Fasciola hepatica total extract (FHTE) had enhanced IL-10 and IL-1RA, but reduced TNF production upon re-stimulation with FHTE or TLR ligands and this was reversed by inhibitors of DNA methylation. In contrast, macrophages trained with β-glucan or BCG had enhanced TNF production upon re-stimulation with Pam3cys or LPS. Furthermore, FHTE-trained macrophages had enhanced expression of markers of alternative activated macrophages (AAM). Macrophages from mice treated with FHTE expressed markers of AAM and had heightened IL-10 and IL-1RA production in response to FHTE or TLR ligands and had suppressed TNF and IL-12p40 production. Macrophages from mice treated with FHTE had reduced APC function and inhibited IL-17 production and the encephalitogenic activity of T cells in the experimental autoimmune encephalomyelitis (EAE) model. In addition, mice pre-treated with FHTE were resistant to induction of EAE and this was associated with a significant reduction in IL-17-producing γδ and CD4 T cells infiltrating the CNS. Our findings reveal that cells of the innate immune system can be trained in vitro or in vivo to be more anti-inflammatory by exposure to helminth products and this protects mice against the induction of a T cell-mediated autoimmune disease.